Predictors of Mortality in Spontaneous Intracerebral Haemorrhage: A Prospective Interventional Study from a Tertiary Care Centre, Kerala, India - Shameej Koloth Vayalipath; Rajeev Mandakaparambil; Prakasan Kannoth; Jaleel Padinhareyiel; Shinihas Vattaparambil; Binu Areekal (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Spontaneous Intracerebral Haemorrhage (SICH) is a potentially life-threatening condition associated with a high mortality and morbidity. Early assessment of outcome is important to optimise the therapeutic efforts. This study helps in the prediction of outcomes in SICH based on clinical and radiological predictors, so as to effectively utilise the treatment resources. Aim: To assess clinical and radiological predictors of mortality and morbidity in patients with SICH at a Tertiary Care Centre, Kerala, India. Materials and Methods: This prospective interventional study included 100 patients admitted with SICH at Government Medical college, Kozhikode, Kerala, India, from 1st May 2019 to 30th January 2020. The assessed variables include age, sex, mean Glasgow Coma Scale (GCS) score on admission, Intracerebral Haemorrhage (ICH) volume, ICH site, ICH score and treatment provided (conservative/surgery). The dependent variable was 30 day mortality. Univariate analysis was performed to determine the association between the mortality and independent variables. A binary logistic regression was also performed. Statistical analysis performed using Statistical Package for the Social Sciences (SPSS) software version 22.0. The p-value <0.05 was considered significant. Results: Among the total of 100 SICH patients, males were 52% and females were 48%; the mean age was 67±11 years. The medical history of SICH patients predominantly showed hypertension (90%), diabetes (45%) and alcohol abuse (33%). Out of total, 70% cases were managed conservatively, and 30% cases were managed surgically. The short-term outcome of 30 day mortality was 40% and the survival rate was 60%. Univariate analysis inferred that the location of bleed (p-value=0.0002), volume of ICH (p-value <0.001), ICH score (p-value 0.003) and type of management (p-value <0.001) were statistically significant predictors for 30 day mortality in SICH patients. Conclusion: The location of bleed, volume of ICH, ICH score and type of management were statistically significant predictors for 30 day mortality in SICH patients.